Sediment dynamics in the Gulf of Lion (NW Mediterranean Sea) during two autumn–winter periods with contrasting meteorological conditions. (January 2023) - Estournel, Claude; Mikolajczak, Guillaume; Ulses, Caroline; Bourrin, François; Canals, Miquel; Charmasson, Sabine; Doxaran, David; Duhaut, Thomas; de Madron, Xavier Durrieu; Marsaleix, Patrick; Palanques, Albert; Puig, Pere; et al.
Graphical abstract: Highlights: Strong interannual variability of the sediment dynamics in the Gulf of Lion. Massive sediment accumulation near the Rhone River mouth (∼56 % of the river inputs) Sediment deficit on the inner shelf due to the long-term reduction of the Rhone inputs. Storm-induced sediment accumulation in the southwestern Gulf of Lion. Cold winters mainly impact the southwestern and outer shelf and the submarine canyons. Abstract: A simulation based on a hydro-sedimentary model was conducted for the period between summer 2010 and spring 2012 in the Gulf of Lion (northwestern Mediterranean Sea) to understand the spatial and temporal variability of sediment transport, erosion and deposition on the continental shelf and slope. Datasets of both simulated and observed current, temperature and suspended matter from the shelf and the Cap de Creus Canyon which is the main export route towards the continental slope, were first compared to assess the reliability of the simulation. The simulation shows the massive sediment accumulation near the Rhone River mouth (∼56 % of the inputs), the accretion along the mid-shelf mud belt, and the impact of dense shelf water cascading on sediment resuspension and erosion inside the Cap de Creus Canyon. The two studied autumn–winter periods were strongly contrasted in terms of meteorological conditions and subsequent impacts on the sediment dynamics. During the first period (2010–2011) dominated by marine storms, the shelf sediment underwent strong changes, the Rhone River sediment load accumulated in a relatively small area, stock of littoral sands moved to the inner shelf (20–40 m) while inner shelf fine particles fed the mid-shelf mud belt and the upper Cap de Creus Canyon. During the second period (2011–2012) with very little marine wind and a particularly cold winter, sediment on the shelf underwent little change except for a southwestward growth of the Rhone River prodeltaic deposit. Sediment from the southwestern end of the shelf as well as from the upper Cap de Creus Canyon was flushed toward deeper reaches by dense shelf water cascading. Cascading also had a more moderate impact in the various canyons incising the continental shelf. Our work supports the view of an unbalanced sedimentary system, with a deficit mainly over the inner shelf, whose main driver is probably the strong and fast reduction of particulate matter inputs from the Rhone River (by a factor of 4 in less than one century).